Observations of Ice Nucleation and Propagation in Plants Using Infrared Video Thermography. - Wisniewski, M. (1997)
We evaluated the use of infrared (IR) video thermography to observe directly ice nucleation and propagation in plants. An imaging radiometer with an HgCdTe long-wave (8-12 [mu]m) detector was utilized to image the thermal response of plants during freezing. IR images were analyzed in real time and recorded on videotape. Information on the videotape was subsequently accessed and analyzed utilizing IR image analysis software. Freezing of water droplets as small as 0.5 [mu]L was clearly detectable with the radiometer. Additionally, a comparison of temperature tracking data collected by the radiometer with data collected with thermocouples showed close correspondence. Monitoring of an array of plant species under different freezing conditions revealed that ice nucleation and propagation are readily observable by thermal imaging. In many instances, the ice nucleation-active bacterium Pseudomonas syringae placed on test plants could be seen to initiate freezing of the whole plant. Apparent ice nucleation by intrinsic nucleators, despite the presence of ice nucleation-active bacteria, was also evident in some species. Floral bud tissues of peach (Prunus persica) could be seen to supercool below the temperature of stem tissues, and ice nucleation at the site of insertion of the thermocouple was frequently observed. Rates of propagation of ice in different tissues were also easily measured by thermal imaging. This study demonstrates that IR thermography is an excellent method for studying ice nucleation and propagation in plants.